2018
DOI: 10.1001/jama.2017.20897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laparoscopic Sleeve Gastrectomy vs Laparoscopic Roux-en-Y Gastric Bypass on Weight Loss in Patients With Morbid Obesity

Abstract: clinicaltrials.gov Identifier: NCT00356213.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
657
7
37

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,044 publications
(794 citation statements)
references
References 34 publications
42
657
7
37
Order By: Relevance
“…We detected two studies that had been performed in the same study population, and of these, only the study referring to a clinical trial registry number was included . Finally, 12 articles of 10 different RCTs, where of four had data on remission at different lengths of follow‐up, were included in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…We detected two studies that had been performed in the same study population, and of these, only the study referring to a clinical trial registry number was included . Finally, 12 articles of 10 different RCTs, where of four had data on remission at different lengths of follow‐up, were included in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…The SLEEVEPASS study [63] reported 57% EWL for RYGB and 49% EWL for sleeve at 5 years. The SM_BOSS study [64] reported 68% excess BMI lost (EBMIL) for RYGB and 61% EBMIL for sleeve. The STAMPEDE study [65] reported 21.7% TWL for RYGB and 18.5% TWL for sleeve.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic sleeve gastrostomy is a popular operation, and in the US, LSG has surpassed Roux-en-Y gastric bypass because of more favorable outcomes of lower mortality and overall morbidity, similar weight loss, and resolution of health comorbidities at 5 years [163][164][165][166]. Further supporting LSG as a preferred procedure is the lower leak rates, the twofold lower complication rate, and a mortality rate that is half that of Roux-en-Y gastric bypass [167].…”
Section: Discussionmentioning
confidence: 99%